ماهية الاستحسان الذي أنكره الشافعي The Reality of al-Istihsan that Was Refuted by al-Shafi'i - السعد (Khalid Khalifa Alsaad), خالد خليفة (At-Tajdid - Intellectual Refereed Journal, 2017)
مستخلص البحث هذه الورقة ليست في بيان حجية الاستحسان وما استدل به مثبتوه أو نافوه، ولا للكشف عن الأسباب التي أنكر لها الشافعي الاستحسان، وإنما هي محاولة للبحث عن ماهية الاستحسان الذي أنكره وشدَّد النكير على القائلين به، أو بتعبير الأصوليين؛ إنها تحرير محلِّ النزاع بين الفريقين. والباعث على اختيار هذا الموضوع ما قرَّره بعض أصحاب المصنفات الأصولية – ولا سيما المعاصرون منهم – من أن النافين للاستحسان لم يتبيَّنوا حقيقته عند القائلين به،ولم يُدركوا مرادهم منه، فظنُّوه من التشريع من غير دليل، فشنُّوا عليه الغارة وقالوا فيه ما قالوا،أو لعل الشافعي قد نُقل إليه معنى الاستحسان عن مالك وأبي حنيفة خطأ، أو أن مراده بذلك ما يستحسنه الإنسان من غير دليل، بل بمجرد الهوى والتشهي. الكلمات الرئيسة: الاستحسان، الحجية، نفي حجية الاستحسان، الشافعي. Abstract This paper is meant neither to explain the legitimacy of inference using the principle of istihsan (juristic preference) and the evidences of its supporters and refuters nor to dig out the reasons of why al-Shafi'i denied the principle of istihsan. Rather, it attempts to elucidate the reality of istihsan that was vehemently denounced by al-ShafiÑī. In the parlance of Usuli scholars, this act is called as letting the topic be freely debated. The motive of choosing this topic is the remarks made by some UÎūlī scholars especially contemporary writers, not least the contemporary scholars, that those who denied the istihsan did not seek for enough proofs from its advocates, did not internalize the idea unequivocally. As a result, they perceived the concept as a kind of 'legislation not backed by evidence' and therefore, hastily attacked its advocates. It is also likely that the reality about istihsan was not successfully transmitted to al-Shafiʿī from Malik and Abu Hanifa, or al-Shafi'i might have believed that the concept is just all about the act of preferring by human being on ground of no proof but only according to his whims. Keywords: al-istihsan, the legitimacy of inference, denial of legitimacy of inferring by istiihsan and al-Shafi'i Abstrak Kertas kerja ini bukan bertujuan menjelaskan kekuatan istihsan sebagai hujah mahupun membentangkan dalil-dalil yang digunakan oleh golongan yang menyokong dan yang menolaknya. Ia juga tidak bertujuan menerangkan tentang sebab-sebab yang mendorong Imam Syafie menolak istihsan. Kajian ini tidak lain hanyalah satu usaha mencari hakikat istihsan yang beliau tolak, atau menurut istilah para ulama usul, ia adalah usaha untuk menjernihkan perselisihan antara dua golongan ini. Dorongan utama tajuk ini dipilih adalah seperti yang dikatakan oleh sebahagian penulis kitab-kitab usul, terutamanya yang kontemporari. Mereka mengatakan bahawa golongan yang menolak istihsan tidak menyelidik dengan terperinci hakikat itihsan di kalangan golongan yang menerimanya. Mereka menyangka istihsan adalah membuat syariat tanpa dalil. Maka dengan itu mereka menolaknya sekeras-kerasnya sehingga kedengaran kata-kata yang mencela penggunaannya. Mungkin Imam Syafie sendiri menerima konsep yang salah daripada Imam Malik dan Abu Hanifah iaitu istihsan adalah perkara yang dirasakan baik oleh manusia tanpa berpandukan kepada dalil, malah hanya dengan hawa nafsu. Kata Kunci: al- istiihsan, hujjah, penolakan hujjah al- istihsan, al-Shafi'i